Modern Trends in Increasing the Energy Efficiency of the Base Station Subsystem - Juraev Nurmakhamad (Zien Journals, 2023)
The modern era of telecommunications is marked by an insatiable demand for connectivity, which has brought to the forefront the urgent need to enhance the energy efficiency of base station subsystems. The base station subsystem serves as the backbone of mobile communication networks and is a significant consumer of power. This article explores contemporary trends in the realm of telecommunications infrastructure to promote a more sustainable and eco-friendly future.
Keywords: Energy Efficiency; Base Station Subsystem; Telecommunications